Schiff Base-Decorated Graphene Oxide as Corrosion Inhibitor for Carbon Steel Type C1025 in Acidic Solution - Naser, Ali Abra (Universitas Gadjah Mada, 2025)
Schiff-base functionalized graphene oxide (GOPT) has garnered significant attention due to its unique properties and promising applications in several fields. The synthesized compounds were characterized using various methods, including Raman shift, FTIR, XRD, EDS, and FESEM. Using the Tafel technique, GOPT was evaluated as a corrosion inhibitor for alloy (C1025) at various temperatures in an acidic solution containing 0.1 M HCl. According to the data, the inhibition of the efficiency of GOPT at 15 ppm concentration at 298 K is 88.6%. Studies on the influence of temperature on the corrosion process between 298 and 308 K showed that efficiency increased with temperature. Activation energy, activation enthalpy, Gibbs free energy of activation, activation entropy, adsorption enthalpy, adsorption entropy, free energy of adsorption, and equilibrium constant were calculated as kinetic and thermodynamic parameters. The adsorption was physically based on the activation energy, and the process was endothermic, as indicated by the enthalpy values. The Gibbs free energy values also determine the inhibitor’s effectiveness in reducing alloy corrosion. GOPT produces a Langmuir adsorption isotherm with an R2 value of approximately 0.95. These results confirm that the GOPT is a good corrosion inhibitor with potential for use in industrial applications requiring protection.